Modeling, sampling and reconstruction of EEG signals with seizures - Leena Bhandari. (2008)
This project focuses on modeling the EEG signal of an infant with seizure as signal with finite rate of innovation (FRI). EEG signals are typically non-bandlimited signals and therefore the classical sampling theorem [1], [2] cannot be applied as it only reconstructs a low pass approximation of the original signal. The sampling theorems for signals with FRI will be applied to sample and reconstruct the modeled EEG signal with seizure.